2018
DOI: 10.1080/17550874.2019.1596172
|View full text |Cite
|
Sign up to set email alerts
|

Olive orchard microbiome: characterisation of bacterial communities in soil-plant compartments and their comparison between sustainable and conventional soil management systems

Abstract: Background: Beneficial bacteria-plant interactions play an important role in agriculture, positively affecting plant status and improving product quality. Bacterial endophytes contribute to host plant protection and survival. Aim: This study characterised the bacterial communities present in soil, leaf surface and xylem sap of olive trees, and investigated their response under a sustainable (Smng) or a conventional (Cmng) management system in an olive grove located in southern Italy. The aims are: (a) to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 66 publications
15
50
1
Order By: Relevance
“…However, while Actinobacteria and Proteobacteria bacteria were present in all three olive genotypes, only "Picual" contained Firmicutes and Bacteroidetes, and only "Acebuche" contained bacteria from the Deinococcus-Thermus phylum. These results are in accordance with those obtained previously following similar approaches from olive leaves and xylem sap (Müller et al, 2015;Fausto et al, 2018;Sofo et al, 2019) as well as from other woody plants, like grapes, oak, poplar, and Pinus (Uroz et al, 2010;Bonito et al, 2014;Cregger et al, 2018;Deyett and Rolshausen, 2019). Interestingly, our results were more in agreement with those obtained by Deyett and Rolshausen (2019) that found similar proportions for Proteobacteria and Actinobacteria on grapevine xylem sap than those on olives obtained by Fausto et al (2018), when using a similar xylem sap extraction method with a Scholander pressure chamber.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, while Actinobacteria and Proteobacteria bacteria were present in all three olive genotypes, only "Picual" contained Firmicutes and Bacteroidetes, and only "Acebuche" contained bacteria from the Deinococcus-Thermus phylum. These results are in accordance with those obtained previously following similar approaches from olive leaves and xylem sap (Müller et al, 2015;Fausto et al, 2018;Sofo et al, 2019) as well as from other woody plants, like grapes, oak, poplar, and Pinus (Uroz et al, 2010;Bonito et al, 2014;Cregger et al, 2018;Deyett and Rolshausen, 2019). Interestingly, our results were more in agreement with those obtained by Deyett and Rolshausen (2019) that found similar proportions for Proteobacteria and Actinobacteria on grapevine xylem sap than those on olives obtained by Fausto et al (2018), when using a similar xylem sap extraction method with a Scholander pressure chamber.…”
Section: Discussionsupporting
confidence: 93%
“…Some differences were also found among those studies at the genus level. Thus, Deyett and Rolshausen (2019) found bacteria in the Enterobacteriaceae family, and belonging to Streptococcus, Bacteroides, Bacillus, Acinetobacter, and Pseudomonas genera as the most abundant on grapewine sap, whereas Fausto et al (2018) identified some bacterial genera in the olive sap common to our study (e.g., Curtobacterium, Hymenobacter, Methylobacterium, and Sphingomonas), although they did not provide their relative abundance. Those differences may be due to the fact that different primers targeting different variable regions of the 16 rRNA were used for amplification in each study, or to the differences on environmental growing conditions and the plant genotypes evaluated.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Indeed, chitinolytic bacteria are well-known antagonists of plant pathogenic fungi [39]. It is well known that bacterial endophytes contribute to the survival and protection of both healthy and stressed fruit plants [40]. In fact, the rhizosphere of wild olive is a reservoir of bacterial antagonists of V. dahliae showing chitinolytic activity [41].…”
Section: Bacteriamentioning
confidence: 99%